The Role of Foreign Investments in the Development of the Country's Economy (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, aspects of the importance of foreign investments in the development of the country's economy. Why is foreign investment important? Also, in the article, the problems encountered in the attraction of foreign investments to the national economy of our country and the need to use measures aimed at preventing these problems are widely covered.